Phylogenetic analysis confirms hepatitis C virus transmission among hemodialysis patients in Kosovo - Jakupi, Xhevat; Mlakar, Jana; Lunar, Maja; Rudhani, Ibrahim; Raka, Lul; Tavakoli, Norma; Poljak, Mario (The Journal of Infection in Developing Countries, 2019)
Introduction: It has recently been demonstrated that there is a very high prevalence of hepatitis C virus (HCV) infection among hemodialysis patients in Kosovo with HCV subtype 1 being the most prevalent subtype. In this study, we further detail the molecular epidemiology of HCV outbreaks occurring in seven dialysis centers in Kosovo. Methodology: In total, 273 samples obtained from HCV RNA positive patients undergoing hemodialysis at one of the seven centers in Kosovo were selected for this study: 171 subtype 1a samples, 91 subtype 4d samples, and 11 subtype 1b samples. A partial HCV NS5B region was amplified and sequenced. Subtype-specific phylogenetic analyses were performed with the inclusion of control sequences and transmission clusters were identified. Results: NS5B sequences were successfully obtained in 257/273 (94.1%) of samples; 162 subtype 1a, 84 subtype 4d, and 11 subtype 1b sequences. Phylogenetic analyses showed a high degree of phylogenetic clustering of HCV sequences subtyped 1a (99.4%), 1b (63.6%), and 4d (76.2%). Distinct phylogenetic clusters of sequences obtained from hemodialysis patients were observed for all three subtypes studied. In addition, several smaller clusters within the large clusters were identified, mainly from a single dialysis center. Conclusions: Phylogenetic analyses confirmed nosocomial transmission during dialysis as a major factor in the spread of HCV at the seven dialysis centers in Kosovo.